Voices from the desert - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
There is something about deserts that makes the mind more fertile. To survive in a desert you have to be creative, and more. So too you must be if you are to protect your arid and semi-arid land against desertification through over-cultivation,...